Digitalización educativa y su influencia en la formación de hábitos de lectura en los estudiantes de educación básica elemental de la Escuela Isidro Ayora - Aspiazu Abad, Meyli Arlines (2025)
Digitalization in education has revolutionized teaching techniques, allowing access to a wide variety of digital resources that enhance the learning process. In the field of reading, the implementation of online platforms and interactive resources has proven to be an effective resource to promote the reading habit in students, providing more dynamic and captivating experiences. In this framework, the purpose of this research is to establish the impact of educational digitalization in the development of reading habits in elementary school students of the Isidro Ayora School. The population will consist of students of the three levels mentioned above (5th, 6th and 7th EGB) together with their respective tutor teachers. For the study, a representative sample of 80 students from parallel “A” of each level and 3 mentor teachers will be chosen, who will provide information about the use of digital tools and their link with the evolution of reading habits. The study will use a combined approach, making use of both quantitative and qualitative techniques to acquire a complete picture of the effect of digitization on reading. Finally, the correct use of digital resources in the teaching process favors the strengthening of reading habits in students, fostering an increase in motivation and interest in reading.